2014
DOI: 10.1590/1807-1929/agriambi.v18n09p934-938
|View full text |Cite
|
Sign up to set email alerts
|

Características agronômicas e teor de óleo da canola em função da época de semeadura

Abstract: Propôs-se, com este trabalho, avaliar a influência das diferentes épocas de semeadura sobre a população de plantas, produtividade e teor de óleo da canola (Brassica napus L.) na safra de 2012. Utilizou-se o delineamento experimental em blocos casualizados, em esquema de parcelas subdivididas 7 x 2, sendo sete épocas de semeadura: 24/03/12; 07/04/12; 21/04/12; 05/05/12; 19/05/12; 02/06/12 e 16/06/12 e dois híbridos: Hyola 61 e Hyola 433. As produtividades e os teores de óleo foram semelhantes entre os híbridos,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 10 publications
1
5
0
3
Order By: Relevance
“…It can also be used as a vegetal covering of the soil, being the species most cultivated in the country Brassica napus L. var. oliferous, where its late cultivation in winter could contribute to optimizing the use of agricultural resources further, also creating another income opportunity for farmers (Milciades et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It can also be used as a vegetal covering of the soil, being the species most cultivated in the country Brassica napus L. var. oliferous, where its late cultivation in winter could contribute to optimizing the use of agricultural resources further, also creating another income opportunity for farmers (Milciades et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Just as Melgarejo et al (2014) found, Hyola 433 performance was impaired as a result of limited water availability observed in May, 2011 (Figure 1), which could have compromised the flowering formation of this shortcycle hybrid.…”
Section: Thousand Seed Weight (Tsw)mentioning
confidence: 73%
“…The mean lipid value expected in Brazil is 380 g kg -1 [6]. In Cfa climate, varying sowing dates, [16] obtained, for two hybrids, values between 346 and 399 g kg -1 .This variation, according to the authors, was correlated with water stress.…”
Section: Resultsmentioning
confidence: 96%